The Progress of Industry 4.0 in the Conditions of a Pandemic - Bulgarian Case in Natural Gas Sector - Biolcheva, Petya; Vasil Bozev, (Journal of Social Transformation and Regional Development, 2022)
Technological digitalization and the capabilities of artificial intelligence are among the main tools recommended to companies to overcome the negative consequences of the economic effects of the COVID-19 pandemic. And this is true not only for companies in the high-tech sector, but also for those who are part of the supply chains of natural resources such as natural gas. Moreover, in addition to the flexibility of technological solutions, natural gas supply companies are expected to protect their place in the renewable / regenerative / economy, which defines natural gas as one of the clean energy sources. To meet these challenges, the article examines how and in what way the ongoing global crisis provoked by the COVID 19 pandemic is slowing down the processes of technological digitalization and integration of business processes in gas supply companies, i.e., to what extent these companies have "walked the path" of the transition from Industry 4.0 to Industry 5.0. We are looking for answers to these questions on the basis of an empirical study conducted in gas companies, showing the change in the level of technological innovation, the development of linkages between individual business processes, and the place of artificial intelligence in their overall activities.